Ohrid, Nordmazedonien. Neue Inschriftenfunde aus Ohrid/Lychnidos (Nordmazedonien). Die Arbeiten der Jahre 2018 und 2019 - Kerschbaum, Saskia; Verčík, Marek (e-Forschungsberichte des DAI, 2023)
Epigraphic studies on the territory of the present Republic of Northern Macedonia have so far been limited primary to the well-known urban centres of the Hellenistic and Roman periods. The findings from the countryside are hardly known to date. In the summer of 2018 and 2019, a survey project was conducted in the region around the Lake Ohrid, which expanded the epigraphic context of the ancient city of Ohrid/Lychnidos. The newly discovered milestone and a tombstone not only inform about the epigraphic habit, but also testify to the intensive development of the region in the 2nd/3rd century AD manifested in the archaeological evidence.